En beredskap för alla? En tematisk analys om ansvarsförskjutningen inom den svenska beredskapspolitiken - Wickström,Johan (2024)
During the past ten years, Sweden's security policy has undergone a clear change, where key events have been Russia's invasion of Ukraine in 2022 and, most recently, Sweden's entry into NATO in 2024. The focus on issues such as national security and military rearmament have increased. The essay discusses how a perceived need to improve resilience has put requirements on the population for better civil preparedness. The essay discusses the shift in responsibility that is now taking place in Swedish security policy visualises inequality in the society. National security was previously mainly seen as a state responsibility, but where the reconstruction of the total defense meant a greater role for civil preparedness. Starting from the theoretical concepts of liberal governmentality and responsibilization, a thematic analysis is then carried out. The three themes that the analysis examines are people's 1. Economic conditions, 2. Demographical conditions and 3. Social conditions and how these can affect people's opportunities to live up to the increasingly higher requirements that a good home preparation entails. The work ends with a discussion where the themes of the analysis and the view on home preparedness are discussed and where the limits for responsibilization within preparedness issues are.
Keywords: National security; total defence; preparedness; inequality; militarization; thematic analysis; responsibilization